Mengeksplorasi Filsafat Materialisme - Dellyana, Dellyana (Journal of Innovation in Teaching and Instructional Media, 2023)
Materialism is a philosophical view or framework of thought which emphasizes that physical substance or matter is the basis of all reality, including thoughts, feelings and natural phenomena. This view rejects or minimizes the role of non-material or spiritual elements in explaining the world. This article provides information in the form of views on the Materialist Philosophical View of Knowledge, Knowledge and Education, using a literature-based research approach and literature study. The research method uses library research analysis to explore and synthesize materialist views from various literary sources. Education in the context of materialism is seen as a means of developing a deeper understanding of material. The focus includes the introduction and mastery of practical skills relevant to natural resource management. The literature study method is used to explore the relevance and applicability of materialist concepts in the framework of contemporary education, explaining the concept of material determinism and its impact on individual freedom.